Evaluation of vegetative growth of forage palm in the Alagoas Semiarid Region - Francisca Márcia França Soares; Ariane Loudemila Silva de Albuquerque; Wesley Reniberg Timoteo Silva (Universidade Estadual de Alagoas, 2021)
The forage palm is adapted to regions with a semi-arid climate, constituting an important source of food for herds in the dry season, especially in Northeast Brazil. The objective was to evaluate the growth of small palm (Opuntia cochenillifera) without an irrigation system due to organic fertilization in the municipality of Santana do Ipanema-AL. The project was carried out in the Serrote dos Braz community, located in the municipality of Santana do Ipanema, mesoregion of the Sertão Alagoano. The experimental design was in randomized blocks, with an arrangement of subdivided plots. The cladodes were planted in a domino shape, testing two types of organic fertilization (cattle and poultry manure). For the evaluation of the vegetative development of the forage palm, the morphometric aspects of the cladodes and plants were observed. The characteristics analyzed in thecladodes were width, length and perimeter, determined with the aid of a measuring tape. The data obtained were subjected to analysis of variance followed by the Tukey test. It was concluded that organic fertilization with poultry manure had a significant effect on all variables studied when compared to bovine manure. Regarding the soil temperature, there was a significant difference in the hours observed during work.